Fatty acid feedstocks enable a highly efficient glyoxylate‐TCA cycle for high‐yield production of β‐alanine. Issue 2 (19th June 2022) - Miao, Yingchun; Liu, Jiao; Wang, Xuanlin; Liu, Bo; Liu, Weifeng; Tao, Yong
Abstract: Metabolic engineering to produce tricarboxylic acid (TCA) cycle‐derived chemicals is usually associated with problems of low production yield and impaired cellular metabolism. In this work, we found that fatty acid (FA) feedstocks could enable high‐yield production of TCA cycle‐derived chemicals, while maintaining an efficient and balanced metabolic flux of the glyoxylate‐TCA cycle, which is favorable for both product synthesis and cell growth. Here, we designed a novel synthetic pathway for production of β‐alanine, an important TCA cycle‐derived product, from FAs with a high theortecial yield of 1.391 g/g. By introducing panD, improving aspA, and knocking out iclR, glyoxylate shunt was highly activated in FAs and the yield of β‐alanine reached 0.71 g/g from FAs, much higher than from glucose. Blocking the TCA cycle at icd/sucA/fumAC nodes could increase β‐alanine yield in a flask cultivation, but severely reduced cell growth and FA utilization during fed‐batch processes. Replenishing oxaloacetate by knocking out aspC and recovering fumAC could restore the growth and lead to a titer of 35.57 g/l. After relieving the oxidative stress caused by FA metabolism, β‐alanine production could reach 72.05 g/l with a maximum yield of 1.24 g/g, about 86% of the theoretical yield. Our study thus provides a promising strategy for the production of TCA cycle‐derived chemicals.